Posterior reversible encephalopathy syndrome - Sumana J Kamath; Priyansha Multani; Madhurima A Nayak (Journal of Clinical Ophthalmology and Research, 2014)
Posterior reversible encephalopathy is a relatively newly recognized disorder, which presents as a complication of pregnancy induced hypertension. Its usual presentation is blurred vision, headache, seizures and disturbance of consciousness. A 20-year-old primigravida presented with seizures, headache and loss of vision in both eyes. She was drowsy and blood pressure was 120/100 mm Hg. Ocular examination was fairly normal, except that her vision was a perception of light and fundus showed early papilledema. She was started on antihypertensives and anticonvulsants. The pregnancy was terminated. A magnetic resonance imaging revealed hyperintense areas in bilateral posterior occipitoparietal regions in T2 weighted images suggestive of posterior reversible encephalopathy syndrome (PRES). She had an improvement of vision starting from the very next day of the presentation. Treatment of this condition involves recognition of the offending factor and its removal. PRES is clinico-neuroradiological diagnosis and its knowledge can help prompt reversal and relief of anxiety to the patient.